Comparative analysis of N-acetyltransferase 2 genotyping results among patients with newly diagnosed pulmonary tuberculosis residing in the Sakha Republic (Yakutia) - N. M. Krasnova; E. N. Efremova; A. A. Egorova; O. I. Filippova; Y. V. Chertovskikh; Z. A. Rudykh; E. A. Alekseeva; T. E. Tatarinova; D. A. Sokorutov; N. S. Val; M. K. Vinokurova; A. F. Karvchenko; et al. (Бюллетень сибирской медицины)
Aim. To assess the variability of the NAT2 gene and to comparatively analyze the prevalence of NAT2 polymorphisms and acetylation types among Yakut and Russian patients newly diagnosed with pulmonary tuberculosis (TB), permanently residing in the Sakha Republic (Yakutia).Materials and methods. The study included 197 patients with newly diagnosed pulmonary TB (132 Yakuts and 65 Russians) aged (43.3 ± 14.4). The following single-nucleotide polymorphisms were analyzed, using real-time polymerase chain reaction (PCR): NAT2*5 (rs1801280, Т341С), NAT2*6 (rs1799930, G590A),  NAT2*7 (rs1799931, G857A), NAT2*11 (rs1799929, C481T), NAT2*12 (rs1208, A803G), and NAT2*13 (rs1041983, C282T). Genetically determined basal metabolic rates were calculated using the NATpred online tool.Results. 75% of residents, both of Yakut and Russian ethnicity, were identified as carriers of NAT2 polymorphic variants known to be related to isoniazid biotransformation. NAT2*6 and *13 allelic variants were more frequent in  Yakuts (occurring in 40.9% and 64.4%, respectively); variants NAT2*5, *6, *11, *12, and *13 were more common in Russians (69.2; 55.4; 67.7; 69.2, and 64.6%, respectively). The NAT2*5, *7, *11, and *12 polymorphisms were found to be significantly ethnicity-dependent. The study established substantial prevalence of medium acetylation type (58.3%) in Yakuts and slow acetylation type in Russians (61.5%). Correlations were shown between ethnicity and different prevalence rates of rapid, medium, or slow acetylation types among patients with TB.Conclusion. The observed NAT2 polymorphism distribution patterns and isoniazid acetylation types among Yakut and Russian patients with newly diagnosed pulmonary TB demonstrated that pharmacologic  responses can be significantly different between ethnic groups. Findings of pharmacogenetic studies in Yakut and Russian populations should be incorporated in clinical practice for personalized administration of isoniazid.